MARESIN 1 PREVENTS LIPOPOLYSACCHARIDE-INDUCED NEUTROPHIL SURVIVAL AND ACCELERATES RESOLUTION OF ACUTE LUNG INJURY. Issue 4 (October 2015) - Gong, Jie; Liu, Hong; Wu, Jing; Qi, Hong; Wu, Zhou-yang; Shu, Hua-qing; Li, Hong-bin; Chen, Lin; Wang, Ya-xin; Li, Bo; Tang, Min; Ji, Yu-dong; et al.
Abstract : ABSTRACT: Acute lung injury (ALI) is characterized by lung inflammation and diffuse infiltration of neutrophils. Neutrophil apoptosis is recognized as an important control point in the resolution of inflammation. Maresin 1 (MaR1) is a new docosahexaenoic acid–derived proresolving agent that promotes the resolution of inflammation. However, its function in neutrophil apoptosis is unknown. In this study, isolated human neutrophils were incubated with MaR1, the pan-caspase inhibitor z-VAD-fmk, and lipopolysaccharide (LPS) to determine the mechanism of neutrophil apoptosis. Acute lung injury was induced by intratracheal instillation of LPS. In addition, mice were treated with MaR1 intravenously at the peak of inflammation and administered z-VAD-fmk intraperitoneally. We found that culture of isolated human neutrophils with LPS dramatically delayed neutrophil apoptosis through the phosphorylation of AKT, ERK, and p38 to upregulate the expression of the antiapoptotic proteins Mcl-1 and Bcl-2, which was blocked by pretreatment with MaR1 in vitro . In mice, MaR1 accelerated the resolution of inflammation in LPS-induced ALI through attenuation of neutrophil accumulation, pathohistological changes, and pulmonary edema. Maresin 1 promoted resolution of inflammation by accelerating caspase-dependent neutrophil apoptosis. Moreover, MaR1 also reduced the LPS-induced production of proinflammatory cytokines and upregulated the production of the anti-inflammatory cytokine interleukin-10. In contrast, treatment with z-VAD-fmk inhibited the proapoptotic action of MaR1 and attenuated the protective effects of MaR1 in LPS-induced ALI. Taken together, MaR1 promotes the resolution of LPS-induced ALI by overcoming LPS-mediated suppression of neutrophil apoptosis.